THE UTILIZATION OF SOCIAL NETWORKING SITE AS COMMUNICATION STRATEGY TO GAIN LISTENER (Study of Radio Buku’s Communication Via Twitter) - Fitria Ayuningtias; Kencana Ariestyani (Jurnal InterAct, 2017)
A book is a form of the oldest media, existing since the start of the written language. The books as one of the mass communication tools have significant roles in building the quality of the country. Therefore, the quality of the books must be considered, books not only for entertaining and to inform but should be able to educate. Furthermore, radio also included in category of the mass communication. As one of means in mass communication, radio is the strongest mass communication. Radio can be accessed by several people simultaneously. Anyone can listen to the radio while doing another activity. In addition, radio also can be accessed by the illiterate people. In developing countries and even countries that underdeveloped, radio become famous because of this characteristic. Along with technology development, radio can be listened through streaming. One of the radios using internet technology is Radio Buku. For theoretical approach, the researcher used the mass communication theory, mass media theory, electronic media theory, internet radio theory, broadcast program theory, Computer Mediated Communication theory and the utilization of Twitter as communication media also communication strategy theory. In this research, the researcher used the qualitative methods, the data collection by using the triangulation data. The summary of the research shows that utilization and optimization of Twitter by Radio Buku as their communication strategy to gain the listener